GAYA KEPEMIMPINAN KEPALA SEKOLAH DI MUARA BUNGO - Apdoludin, Apdoludin; Junaidi, Junaidi; Rita Zunarti; Iri Hamzah; Khairul Saleh (Jurnal Cakrawala Ilmiah, 2023)
This research is a descriptive qualitative research. The subjects in this study were school principals, teachers and students of class V and students of class VI in 2021. The data collection techniques used in this study were observation, interviews and documentation. Data were analyzed using data reduction, data presentation and conclusion. The technique of checking the validity of the data is by using source triangulation and technical triangulation. The results showed that the leadership style used by the principal at SDN 98/II Muara Bungo, Pasar Muara Bungo District, Bungo Regency tended to be a Transformational leadership style, in which decisions were always made in meetings, discussions and deliberations with staff and teachers. The principal always accepts opinions, criticisms and suggestions from subordinates well, gracefully and sincerely and actively participates in every activity in the school. The principal always develops and prioritizes a sense of unity and oneness such as togetherness and cohesiveness.